Four new resorcinol derivatives with neuroprotective activities from Xylaria nigripes. Issue 6 (19th March 2022) - Li, Lan-Qing; Li, Jing; Long, Hong-Ping; Liu, Ji-Kai; Wang, Xian
Abstract: Four new resorcinol derivatives, namely (−)/(+)-xylarinig A (1 ), as well as xylarinigs B (2 ) and C (3 ), were isolated from the ethyl acetate extracts of the solid fermentation of Xylaria nigripes . Their structures were established by comprehensive spectroscopic analysis combined with electronic circular dichroism (ECD) calculations. Compound 1 is an optical mixture, and was resoluted into optical pure enatiomers (+)-1 and (−)-1 by chiral HPLC. The neuroprotective effects of 1 –3 against the damage of PC12 cells induced by oxygen and glucose deprivation (OGD) were evaluated. Graphical Abstract: